Industrial minerals and their uses : a handbook and formulary - Ciullo, Peter A., 1954- (Noyes Publications, 1996)
A cross-industry resource for formulators and compounders, and reference for the producers of formulated commodities and industrial minerals. Monographs on each of the common functional industrial minerals-asbestos, barite, calcium carbonate, diatomite, feldspar, gypsum, hormite, kaolin, mica, nepheline syenite, perlite, pyrophyllite, silica, smectite, talc, vermiculite, wollastonite, and zeolite include an overview of natural and commercial varieties, market size, and application areas. These are supported by descriptions of mineral structures, and the wedding of minerals and chemicals through mineral surface modification.
Keywords: Inorganic compounds -- Industrial applications -- Handbooks, manuals, etc.; elektronické knihy; electronic books